Development of a microbial consortium for dairy wastewater treatment - Mazzucotelli, Cintia Anabela (2014)
The wastewater from the dairy industries usually contains high concentrations of contaminants and, since the volume generated is also high, the total contaminant load is very significant. Among the available options for treatment, biological degradation looks like the most promising one. Furthermore, the supplementation of the native microbial populations with external microorganisms with high specific degradation rates (bio-augmentation) has demonstrated to improve the performance of treatment. The main objective of this research was to select a combination of bacteria to improve the aerobic treatment of dairy processing wastewater. For this purpose, eleven fat/protein-degrading microorganisms belonging to the genera Bacillus, Serratia, Lactococcus, Enterococcus, Stenotrophomonas, Klebsiella and Escherichia, were evaluated as potential degrading bacteria using a Plackett-Burman design. Assays were carried out to select the strains that most significantly influenced the degradation of wastewater and biomass yield, in terms of COD removal. A simulated dairy industry effluent was used as culture medium. Four strains were selected as potential members of the microbial consortium: Lactococcus garvieae, Bacillus thuringiensis, Escherichia coli and Stenotrophomonas sp. The optimal operation temperature and pH range of the selected consortium were 32°C and 6 ∼ 8, respectively. The degradation percentages reached with the selected consortium were 80.67 and 83.44% at 24 and 48 h, respectively. The selected consortium significantly improved the degradation of the dairy wastewater, and the degradation degree achieved by this consortium was higher than by using the strains individually.